Hydrogel scaffolds in the treatment of spinal cord injury: a review - Cai, Manqi; Chen, Liji; Wang, Tao; Liang, Yinru; Zhao, Jie; Zhang, Xiaomin; Li, Ziyi; Wu, Hongfu (Frontiers in Neuroscience, 2023)
Spinal cord injury (SCI) is a disease of the central nervous system often caused by accidents, and its prognosis is unsatisfactory, with long-term adverse effects on patients’ lives. The key to its treatment lies in the improvement of the microenvironment at the injury and the reconstruction of axons, and tissue repair is a promising therapeutic strategy. Hydrogel is a three-dimensional mesh structure with high water content, which has the advantages of biocompatibility, degradability, and adjustability, and can be used to fill pathological defects by injectable flowing hydrophilic material in situ to accurately adapt to the size and shape of the injury. Hydrogels mimic the natural extracellular matrix for cell colonization, guide axon extension, and act as a biological scaffold, which can be used as an excellent carrier to participate in the treatment of SCI. The addition of different materials to make composite hydrogel scaffolds can further enhance their performance in all aspects. In this paper, we introduce several typical composite hydrogels and review the research progress of hydrogel for SCI to provide a reference for the clinical application of hydrogel therapy for SCI.